1987
DOI: 10.1021/jm00395a002
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted 1,2,3,4,4a,5,6,10b-octahydrobenzo[f]quinolines and 3-phenylpiperidines: effects on central dopamine and .sigma. receptors

Abstract: N-Substituted analogues of trans-7- and trans-9-hydroxy-1,2,3,4,4a,5,6,10b-octahydrobenzo[f]quinoline (trans-7- and trans-9-OH-OHBQ) were tested for dopamine (DA) D2 receptor affinity by using in vitro [3H]spiperone and in vivo 5,6-di-n-Pr-ADTN binding assays. Potencies at central pre- (auto-) and postsynaptic DA receptors were determined by a biochemical and a behavioral method, respectively. Corresponding data were included for analogous, resolved 3-(3-hydroxyphenyl)piperidines and a few other substituted, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…Even though the compound (±)- 8 possessed higher potency, it lacked high selectivity for the D3 receptor (Table 1). The trans -7-hydroxy-N- n -propyl derivatives were reported to be more active than their cis counterparts in this structural class 17a. Also, the change from n -propyl to n -butyl substitution was reported to increase activity.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Even though the compound (±)- 8 possessed higher potency, it lacked high selectivity for the D3 receptor (Table 1). The trans -7-hydroxy-N- n -propyl derivatives were reported to be more active than their cis counterparts in this structural class 17a. Also, the change from n -propyl to n -butyl substitution was reported to increase activity.…”
Section: Resultsmentioning
confidence: 98%
“…This is largely attributed to the protonated amino group being unfavorably positioned to interact with the key aspartate residue in the cis conformation 15. Compounds that showed activity in the functional assays had hydroxyl group substitution at either the 6 position [for benzo[ g ]quinolines ( 2 , Figure 1)] or the 7/9 position for benzo[ f ]quinolines ( 1 and 3 , Figure 1), corresponding to the α-and β-rotameric forms, respectively 15,17a. In this regard, it is important to mention that to the best of our knowledge no systematic receptor binding studies for DA receptor subtypes (D2 and D3) have been reported with these constrained derivatives and hence, there is a lack of information on precise binding affinity of these derivatives with the respective receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Initially Wikström and coworkers [26] reported that replacing the aromatic ring hydroxyl group of (-)-3-PPP with CF 3 resulted in a compound with weak dopamine receptor antagonist properties judged from effects on dopamine turnover. An increase in motor activity was observed concomitant with the increased dopamine neuronal activity and the compound was suggested to be a preferential dopamine autoreceptor antagonist.…”
Section: Partial Dopamine Receptor Antagonistsmentioning
confidence: 99%
“…The compounds thus synthesised were (-)-DS121 and (-)-OSU6162 and they too behaved, biochemically and behaviorally, as preferential dopamine autoreceptor antagonists, or as we prefer to call them now partial dopamine receptor antagonists. Thus, it was concluded that the replacement of a hydrogen bond donor, such as a hydroxyl group, on the aromatic ring of (-)-3-PPP to an electron-drawing group, such as CF 3, CN or SO 2 CH, was important in converting a partial dopamine agonist to an antagonist [26,27]. It should be noted that the racemic form of DS121 had several years previously been observed to lack intrinsic activity on dopamine receptors [8].…”
Section: Partial Dopamine Receptor Antagonistsmentioning
confidence: 99%
“…In the following example from the literature [39] , the correlation with lipophilicity is studied for 47 compounds in two series which have been designed for dopamine D 2 receptor affi nity. As seen in Fig.…”
Section: Correlated Propertiesmentioning
confidence: 99%